2013
DOI: 10.1002/wrcr.20551
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate assessment of droughts: Frequency analysis and dynamic return period

Abstract: [1] Droughts, like floods, are extreme expressions of the river flow dynamics. Here, droughts are intended as episodes during which the streamflow is below a given threshold, and are described as multivariate events characterized by two variables: average intensity and duration. In this work, we introduce the new concept of Dynamic Return Period, formulated using the theory of Copulas, and calculated via a Survival Kendall's approach. We show how it can be used (i) to monitor the temporal evolution of a drough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
90
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(98 citation statements)
references
References 43 publications
(70 reference statements)
0
90
0
Order By: Relevance
“…The impact of drought cannot be fully described by a single variable (e.g. De Michele et al, 2013;Shiau et al, 2007): analyses have been carried out which consider drought severity, duration (Shiau et al, 2007), maximum deficit (Saghafian and Mehdikhani, 2013), as well as the affected area (Serinaldi et al, 2009). Another example of CE includes fluvial floods resulting from extreme rainfall occurring on a wet catchment (Pathiraja et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of drought cannot be fully described by a single variable (e.g. De Michele et al, 2013;Shiau et al, 2007): analyses have been carried out which consider drought severity, duration (Shiau et al, 2007), maximum deficit (Saghafian and Mehdikhani, 2013), as well as the affected area (Serinaldi et al, 2009). Another example of CE includes fluvial floods resulting from extreme rainfall occurring on a wet catchment (Pathiraja et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For design purposes, rainfall intensity-duration-frequency (IDF) curves have been used for a long time to synthesize the design storm. Therefore, many studies have integrated drought severity and duration based on the multivariate theory (Bonaccorso et al, 2003;GonzĂĄlez and ValdĂ©s, 2003;Mishra and Singh, 2009;Song and Singh, 2010a, b;De Michele et al, 2013). However, these studies cannot fully explain droughts without considering the frequency, which resulted in the development of drought isoseverity curves for certain return periods and durations for design purposes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been widely applied to various aspects of hydrological studies [13]. The main applications of the Copula Function include the analysis of: precipitation characteristics [12], the correlation between flood peak and flood volume [14,15], the frequency and recurrence interval of floods [16][17][18], characteristics of storms [19,20], the frequency and recurrence intervals of droughts [21], drought assessment [22], risk assessment [23], and an assessment of environmental hydrological model performance [24]. Due to the specialty of the water table, the establishment of the Copula Function for this purpose is relatively difficult; therefore, no research that uses the Copula Function to analyze the water table has been reported.…”
Section: Introductionmentioning
confidence: 99%